Porous Fe−N−C Aerogels Derived from Metal‐Organic Aerogels as Electrocatalysts for the Oxygen Reduction Reaction. Issue 10 (25th October 2022) - Wang, Yujun; Tu, Rongxiu; Hou, Chuantao; Wang, Zonghua
Abstract: Synthesis of Fe−N−C electrocatalysts by pyrolysis of porous materials has been shown to be a promising pathway for the oxygen reduction reaction (ORR). Metal‐organic aerogels (MOAs) with unique micropores and mesopores should provide an excellent precursor for Fe−N−C electrocatalysts. This work reports a Fe−N−C aerogel synthesized by pyrolysis of MOA. The Fe−N−C aerogel shows excellent ORR performance in alkaline condition with an onset potential of 0.96 V (vs. RHE) and a limiting current density of 5.02 mA cm −2 . The markedly enhanced ORR performance for Fe−N−C aerogel can be assigned to the synergistic catalytic effect between Fe−N catalytic sites and graphitized carbon and excellent mass transport due to the unique hierarchically porous architecture. In addition, satisfactory durability and methanol tolerance were obtained, demonstrating a promising material for ORR. Abstract : A porous Fe−N−C aerogel catalyst was synthesized by pyrolysis of porous metal‐organic aerogels. The Fe−N−C aerogel shows enhanced catalytic performance for oxygen reduction reaction (ORR) under alkaline condition. The markedly enhanced ORR performance for Fe−N−C aerogel can be assigned to the synergistic catalytic effect between Fe−N catalytic sites and graphitized carbon and excellent mass transport due to the unique hierarchically porous architecture.